Asylum Related Organisations in Europe Networks and Institutional Dynamics in the Context of a Common European Asylum System (Volume 1) - Mratschkowski, Anna (Nomos Verlagsgesellschaft mbH & Co. KG, 2017)
Asylum and refugees in Europe - who can fix a broken system? In times of increasing waves of migration, collective bodies and their cooperation networks are of particular importance to the European asylum system. But who are those actors and what is their contribution to effecting a change in the situation of those seeking refuge in Europe? While the Common European Asylum System introduced standardised regulations for all EU-member states, the real situation in each country differs greatly from those official declarations, even leading to a humanitarian crisis at times. Using the theory of neo-institutionalism, current data from expert interviews, and website and document analyses from Italy, Spain, Greece, Cyprus, Malta and Germany, this study answers those questions. It illustrates how and if this gap between talk and action can be narrowed, how asylum-related organisations and their networks function and how far they contribute to this process. With contributions by: Remonda Balje, Alexander Bauhus, Charlotte Becker-Jamme, Tobias Breuckmann, Megan Costello, Amanda Culver, Dea Dhima, Giselaldina Duro, Lara Elliott, Thomas Hoppe, Lana Horsthemke, Timo Kemp, Jana Komorowski, Melisa Lehmann, Stefan Letmathe, Alona Mirko, Anna Mratschkowski, Judith Nitsche, Thomas Norpoth, Jakob Reckers, Elodie Scholten, Mats Schulte, Davide Scotti, Sara Stojani, Friederike Vogt, Julia Werner, Gerrit Zumstein